The relationship between technological pedagogical content knowledge and belief among preservice mathematics teachers - Hidayat, Riyan; Zainuddin, Zamzami; Mazlan, Nurul Hijja (Elsevier, 2024)
The increasing interest in exploring beliefs about teaching mathematics with technology has led educators to employ belief systems as a framework for understanding the impact of technology on math instruction. However, the complex nature of pre-service teachers' beliefs in teaching mathematics with technology involves various dimensions. This study aims to investigate the predictive relationship between Technological Pedagogical Content Knowledge (TPACK) sub-components and beliefs in teaching mathematics with technology, revealing a statistically significant direct impact. Utilizing a correlational research approach, we collected data from a cohort of 159 Malaysian pre-service teachers with a focus on mathematics education. Structural Equation Modelling (SEM) was employed to analyze the proposed model. The measurement model exhibited a satisfactory fit with the collected data. Notably, technological knowledge (25 %), technological pedagogical content knowledge (69 %), and technological content knowledge (39 %) significantly influence discovery learning, while technological knowledge (24 %), technological pedagogical content knowledge (74 %), and technological content knowledge (30 %) significantly influence multiple representations. This underscores the critical role of TPACK in shaping educators' perspectives and practices, providing a crucial avenue for enhancing technology integration in teaching mathematics.